Retrospective analysis of pneumothorax after repair of esophageal atresia/tracheoesophageal fistula - Jiawei Zhao; Shen Yang; Siqi Li; Peize Wang; Yanan Zhang; Yong Zhao; Kaiyun Hua; Yichao Gu; Junmin Liao; Shuangshuang Li; Yongwei Chen; Jinshi Huang (BMC, 2021)
Abstract Background To analyze the possible causes, treatment and outcomes of postoperative pneumothorax in patients with Gross type C esophageal atresia/tracheoesophageal fistula (EA/TEF). Methods Medical records of patients with Gross type C EA/TEF who were diagnosed and treated in Beijing Children's Hospital from January 2007 to January 2020 were retrospectively collected. They were divided into 2 groups according to whether postoperative pneumothorax occurred. Univariate and multivariate logistic regression analysis were performed to identify risk factors for pneumothorax. Results A total of 188 patients were included, including 85 (45 %) in the pneumothorax group and 103 (55 %) in the non-pneumothorax group. Multivariate logistic regression analysis showed that postoperative anastomotic leakage [P < 0.001, OR 3.516 (1.859, 6.648)] and mechanical ventilation [P = 0.012, OR 2.399 (1.210, 4.758)] were independent risk factors for pneumothorax after EA/TEF repair. Further analysis of main parameters of mechanical ventilation after surgery showed that none of them were clearly related to the occurrence of pneumothorax. Among the 85 patients with pneumothorax, 33 gave up after surgery and 52 received further treatment [conservative observation (n = 20), pleural puncture (n = 11), pleural closed drainage (n = 9), both pleural puncture and closed drainage (n = 12)]. All of the 52 patients were cured of pneumothorax at discharge. Conclusions Anastomotic leakage and postoperative mechanical ventilation were risk factors for pneumothorax after repair of Gross type C EA/TEF, but the main parameters of mechanical ventilation had no clear correlation with pneumothorax. After symptomatic treatment, the prognosis of pneumothorax was good.